Physical Model Study on Wave Attenuation Effects of Forest against Wave Wash on Horizontal and Gentle Slope Beaches - ZHANG Zhilin; HUANG Bensheng; LIU Da; HONG Changhong; HU Tao (Renmin Zhujiang)
This study systematically investigated the variation patterns of key hydrodynamic parameters, including wave height, wave pressure, plant stem force, and three-dimensional (3D) flow velocity through large-scale physical model experiments of wave flumes conducted under two terrain conditions: horizontal and 1:20 gentle slope beaches. The influence of different beach morphologies in estuarine and coastal areas on wave attenuation effects of forest against wave wash was explored. Results show that under experimental regular wave conditions, beach morphology exerts no significant impact on the wave attenuation effect. Within the shelterbelt width range of 0.5–6.0 m, the differences in wave height, wave pressure, stem force, and flow velocity damping rates between the two terrains remain below 10%. This research confirms the limited influence of beach topography on vegetation-controlled wave attenuation. The wave attenuation calculation method established for horizontal beach conditions demonstrates significant applicability to gentle slope terrains, providing support for rational planning of shelterbelt widths and optimization of protective benefits in coastal engineering practices.